2009
DOI: 10.1016/j.nurt.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids as Pharmacotherapies for Neuropathic Pain: From the Bench to the Bedside

Abstract: Summary:Neuropathic pain is a debilitating form of chronic pain resulting from nerve injury, disease states, or toxic insults. Neuropathic pain is often refractory to conventional pharmacotherapies, necessitating validation of novel analgesics. Cannabinoids, drugs that share the same target as ⌬ 9 -tetrahydrocannabinol (⌬ 9 -THC), the psychoactive ingredient in cannabis, have the potential to address this unmet need. Here, we review studies evaluating cannabinoids for neuropathic pain management in the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(229 citation statements)
references
References 183 publications
(234 reference statements)
4
220
0
5
Order By: Relevance
“…47,48 Research has demonstrated that cannabinoids are useful in treating anorexia associated with cancer, nausea and vomiting associated with chemotherapy, chronic pain, and multiple sclerosis. [49][50][51][52] A recently published study also demonstrated that current marijuana use was associated with lower levels of fasting insulin, lower homeostasis model assessmentestimated insulin resistance, and smaller waist circumference. 53 Two recently published review articles on medical marijuana for digestive disorders and select neurologic disorders generally noted small numbers of studies and mixed results.…”
Section: Research Findings On Pharmaceutical Cannabinoids and Medicalmentioning
confidence: 94%
“…47,48 Research has demonstrated that cannabinoids are useful in treating anorexia associated with cancer, nausea and vomiting associated with chemotherapy, chronic pain, and multiple sclerosis. [49][50][51][52] A recently published study also demonstrated that current marijuana use was associated with lower levels of fasting insulin, lower homeostasis model assessmentestimated insulin resistance, and smaller waist circumference. 53 Two recently published review articles on medical marijuana for digestive disorders and select neurologic disorders generally noted small numbers of studies and mixed results.…”
Section: Research Findings On Pharmaceutical Cannabinoids and Medicalmentioning
confidence: 94%
“…The potential use of cannabinoids to treat pain and their limitations have been widely discussed in review and opinion publications (eg, Rahn and Hohmann, 2009). Adverse effects of cannabinoids that can limit their therapeutic use are negative subjective effects and impaired cognition (as discussed in Haney, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Cannabis contains δ-9-tetrahydrocannabinol that is associated with alleviation of pain and has been used therapeutically in various cultures for medicinal purposes.…”
Section: Laboratory Monitoring Of Therapeutic Smokingmentioning
confidence: 99%
“…43 Further, the smoker"s paradox acknowledges the substantial benefits of therapeutic smoking, which has contributed to adoption of therapeutic smoking and development of new drugs. [40][41][42][43][44][45] Therefore, there are justifiable reasons for clinical laboratory testing of smoking toxicity not limited to evidence-based pathology for early identification and intervention of subclinical pathology in smokers but also laboratory monitoring of therapeutic smoking.…”
Section: Laboratory Monitoring Of Therapeutic Smokingmentioning
confidence: 99%